Visualizing a Vibrio cholerae O1 El Tor typing bacteriophage belonging to the Myoviridae group and the packaging of its genomic ends inside the phage capsid. Issue 11 (18th August 2018) - Sen, Anindito; Ghosh, Amar N.
Abstract : Phage D10, an O1 El Tor tying vibriophage, has been successfully employed to tract the outspread of cholera epidemic. Using Transmission Electron Microscopy and computational image analysis, we have determined the structures of the capsid, head-to-tail connector, the contractile helical tail, the baseplate and combined them to form the complete three-dimensional (3D) D10 phage structure. Using partial denaturation experiments on the genome and using the computed 3D structure of the phage, we have established the packing of the genome ends inside the capsid together with the release styles during the phage infection, respectively. Finally, using the 3D density maps of the different components of the D10 phage, we have presented a simplified picture of morphogenesis of the D10 vibriophage. Using the complete assembled structure of the D10 phage, we have traced the path of the phage genome during the infection process, all the way from the phage head down the tail tube of the tail to the top of the baseplate. To the best of our knowledge, this is first structural study for a long-tailed vibriophage. We have tabulated the structural features of the different components of the phages belonging to the Myoviridae and Siphoviridae. The comparative study suggested the possibility of a common origin of the bacteriophages, irrespective of belonging to different groups and species.